PENGARUH BUDAYA KERJA TERHADAP PERSEPSI KESELAMATAN PADA PEKERJA KONSTRUKSI DI INDUSTRI MINYAK DAN GAS - Bagos Armansyah; Albani Musyafa; Fitri Nugraheni; Hari Purnomo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
Occupational safety is a crucial aspect in the oil and gas industry, especially in the high-risk field construction sector. This study aims to analyze the influence of work culture on the perception of safety in field construction workers, especially in the work area of Riau province. The method used was a qualitative and quantitative approach by distributing questionnaires to 108 workers in oil and gas construction projects. The data were analyzed using linear regression to measure the relationship between work culture and safety perception. The results of the study showed that work culture has a positive and significant influence on safety perception, where work culture contributes to safety perception by 45.9%. These findings indicate that a strong work culture can improve the perception of safety, thereby reducing the risk of accidents. Therefore, companies in the oil and gas industry are advised to consistently foster a work culture that supports safety to minimize the risk of work accidents